Factors influencing income inequality across urban Argentina (1998-2003) - María Emma Santos (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This paper tries to disentangle the most relevant determinants of spatial inequality in the urban areas of Argentina. The analysis is restricted to the period 1998-2003. The study is performed with a Panel Data approach using a random effects model. Results suggest that human capital, measured by rates of education completion, is an important contributor to spatial inequality. High rates of primary education appear to reduce inequality while higher rates of secondary education appear to increase it. Labor market characteristics also play a role: urban areas with higher unemployment rates, higher returns to education and a lower percentage of people employed in the secondary sector tend to have higher levels of inequality. Also, dependency and the percentage of people with unsatisfied basic needs have increasing-inequality effects. Finally, there seems to be a relationship between inequality and the level of development, though not with a clear inverted-U pattern as hypothesized by Kuznets. Results are robust to different measures of inequality and different income specifications.
Keywords: D31; I21; 330; Regionale Einkommensverteilung; Stadtregion; Disparitätsmaß; Argentinien